L'Influence de la Relation Père-Fille sur l'Estime de Soi de la Femme Adulte - Morneau, Charlotte; Spain, Armelle (Canadian Journal of Counselling and Psychotherapy, 2011)
This conceptual paper, based on an examination of the theoretical and empirical literature, aims at a better understanding of the influence of father-daughter relationship on the selfesteem of the daughter later as an adult woman. Implications are discussed as to future research, education and counselling.